Tantangan Kesetaraan terhadap Budaya Patriarki di Institusi Pendidikan: Perspektif Mahasiswi FPEB UPI - Hanifah, Ajeng Mulla; Heryani, Irsa Nur Azizah; Firmansyah, Reinata Luciana; Budiyanti, Nurti (Jurnal Pendidikan Islam, 2025)
This study aims to analyze the perspectives of Muslimah students of the Faculty of Economics and Business Education (FPEB), Universitas Pendidikan Indonesia (UPI) batch 2023 towards the challenges of gender equality in a patriarchal culture. Using a quantitative descriptive method, data were collected through questionnaires distributed to respondents. The results showed that patriarchal culture still strongly influences the role and position of women in society, especially in social and professional aspects. As many as 64% of respondents agreed with the statement that women's roles are still limited by social norms, feeling that they are considered less competent than men. The study also found that women are often associated with weakness or dependence on men. These findings suggest the need for greater efforts to address gender stereotypes and encourage more inclusive equality. This research is expected to make theoretical and practical contributions in enriching the study of gender equality as well as recommendations for educational institutions to create an environment that supports women's empowerment.